1990
DOI: 10.1177/089686089001000112
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis-Related Deaths in Continuous Ambulatory Peritoneal Dialysis (CAPD) Patients

Abstract: A total of 636 episodes of peritonitis occurred in 440 patients who entered our continuous ambulatory peritoneal dialysis (CAPD) program from September 1977 to February 1988. Sixteen patients (8 male and 8 female, aged 37–77 years) died during an episode of peritonitis (fatality rate 2.5%). They had been on CAPD for 3 to 105 (average 39) months. Six of them were diabetics. The peritonitis rate among these 16 patients were 1 episode per 12 patient months, while the corresponding figure for the whole (440) CAPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 3 publications
3
25
1
Order By: Relevance
“…Local application of mupirocin ointment at the catheter exit site can prevent exit-site infection and peritonitis involving gram-positive organisms (14). In the present long-term Peritonitis is the most important complication of chronic PD, causing significant morbidity and mortality (23,24). Peritonitis associated with concurrent exit-site or tunnel infection is more likely to proceed to catheter loss (25).…”
Section: Discussionmentioning
confidence: 99%
“…Local application of mupirocin ointment at the catheter exit site can prevent exit-site infection and peritonitis involving gram-positive organisms (14). In the present long-term Peritonitis is the most important complication of chronic PD, causing significant morbidity and mortality (23,24). Peritonitis associated with concurrent exit-site or tunnel infection is more likely to proceed to catheter loss (25).…”
Section: Discussionmentioning
confidence: 99%
“…In severe peritonitis or that which persists despite appropriate antibiotic treatment, one should not hesitate to remove the catheter in order to prevent peritoneal membrane failure and death (9). In such cases, we should establish safe ways (catheters coated with antibiotics?)…”
Section: Prevention Of Peritonitismentioning
confidence: 99%
“…Numerous studies demonstrated that if dialysate WBC are more than 100 cells/mm 3 at day 5 after treatment, the chance of treatment failure is high [ 7 9 ]. Consequently, the International Society of Peritoneal Dialysis (ISPD) defined the term “refractory peritonitis” as failure of dialysate WBC clearance after five days of antibiotic treatment and recommended removing the peritoneal catheter and stopping dialysis therapy in order to prevent morbidity and mortality associated with treatment failure [ 10 , 11 ]. However, in some places where the hemodialysis resource is limited or the dialysis catheter is not readily removable, clinicians might choose to continue antibiotic treatment in selected patients who may have a delayed response to the treatment even though the target of dialysate WBC after the fifth day was not reached.…”
Section: Introductionmentioning
confidence: 99%